New horizons in geodiversity and geoheritage research: Bridging science, conservation, and development - Kubalíková Lucie; Vandelli Vittoria; Pál Márton (Moravian Geographical Reports)
Geodiversity and geoheritage research has gained increasing prominence in natural and social sciences, reflecting their critical role in nature conservation, regional development, geosystem services, and environmental change. Given the inter- and transdisciplinary character of the geodiversity and geoheritage studies, a notable shift from the basic mapping, description and assessment of particular geosites to more advanced and sophisticated methods and approaches is evident during last years. Emerging research themes include quantitative analyses of geodiversity-biodiversity relationships, the dynamics of geomorphosites, innovative degradation risk assessment methodologies tailored to varying conditions, geotourism assessments in specific areas, and the application of geodiversity concepts in environmental policy and management. Additionally, integrating GIS and IT tools has enhanced the evaluation of geodiversity elements in landscape structures and ecosystem services. This article provides a brief reflection on the new directions and methods in geodiversity and geoheritage research and serves as an introduction to the Special Issue of Moravian Geographical Reports on ‘Geodiversity and Geoheritage: Bridging Science, Conservation, and Development’. Generally, it can be stated that the papers included in this special issue reflect the necessity of interdisciplinary approaches to address contemporary challenges in geodiversity and geoheritage conservation and management.